ANTUSIAS KEWIRAUSAHAAN UMKM TERHADAP BISNIS ONLINE DI MASA PANDEMI: Dengan pemaparan yang sudah dijelaskan maka jurnal ini penulis akan membahas terkait dengan pentingnya pengembangan produktivitas kewirausahaan dimasa pandemi Covid 19 terhadap bisnis online yang marak diperbincangkan disektor ekonomi bagi kehidupan masyarakat serta juga upaya dari pemerintahanya terhadap UMKM (Usaha Mikro Kecil Menengah) pada pandemi covid 19 ini. - Anggraeni, Firda Auliyah (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
This research is a study that aims to stay afloat during the Covid 19 pandemic by doing business online. even MSMEs have been diverted to online businesses so that productivity can develop online businesses and also the government's efforts towards MSMEs in current conditions. Because of the enthusiasm of people who use gadgets as something useful and beneficial for the economy. Then for the data writers using secondary data and for the approach with a juridical-normative approach with a library research approach. And for the analytical method, the author uses qualitative methods by analyzing data, searching, and collecting references from various literatures, articles, research journals and on websites about the importance of productivity development during the Covid 19 pandemic for online business which is widely discussed in the economic sector for people's lives. even the millennial generation has turned to online business and is also related to the role of the government during the pandemic against MSMEs. With this online business being able to survive the pandemic. By actively selling, consistently and frequently visiting various social media such as Instagram, Tik tok, Facebook, whatsapp, telegram, Twiter and can also be developed in Shopee, Lazada, Tokopedia, Blibli etc. buying and selling applications. In addition, the role of the government that has been carried out with programming policies to provide incentives for increasing working capital costs, placing the Ministry of SOEs and local governments to support MSMEs has also been efficient.